FINDRISK Questionnaire Combined with HbA1c Testing as a Potential Screening Strategy for Undiagnosed Diabetes in a Healthy Population - Martin, E.; Ruf, E.; Landgraf, R.; Hauner, H.; Weinauer, F.; Martin, S. (Hormone and Metabolic Research, 2011)
Despite the efforts to control the epidemic of diabetes the total number of people living with diabetes is still steadily rising. In order to detect people at risk, cost-effective, convenient, and sensitive screening tools to assess the diabetes risk and to detect undiagnosed type 2 diabetes need to be developed and implemented in the primary care setting. To evaluate the combination of the well established FINDRISK questionnaire and HbA1c testing as a potential screening strategy the data obtained from 671 blood donors were analyzed for a potential correlation with the results of an oral glucose tolerance test. Based on the oral glucose tolerance test, 65 blood donors (9.7%) were newly diagnosed with diabetes, 336 (50.1%) with prediabetes, and 270 (40.2%) had a normal test result. Of the 401 blood donors diagnosed with prediabetes or diabetes 322 (80.3%) had a HbA1c between 5.7% and 6.4% and 27 (6.7%) with a HbA1c of 6.5% or greater. The majority of the blood donors newly diagnosed with diabetes or prediabetes (n=327) had a FINDRISK result of 12 points or higher. ROC analyses confirmed that the optimal cut off levels were for FINDRISK ≥ 12 points and for HbA1c ≥ 5.9%. Thus, a 3-step screening strategy applying the FINDRISK questionnaire followed by HbA1c testing and performing an oral glucose tolerance test on selected individuals could be a cost-saving approach for screening large populations and identifying people at risk for diabetes or undiagnosed diabetes.
Keywords: type 2 diabetes; prevention; screening; early diagnosis; epidemiology